Distribution of the riverine benthic macroinvertebrate community along the citarum cascading dam system in West Java, Indonesia - Barti Setiani Muntalif; Nurul Chazanah; Fikri Ilmi; Navisya Eka Sari; Satria Wira Bagaskara (Global Ecology and Conservation, 2023)
Dam operation is vital for human existence but has several negative impacts on the environment, such as excessive release of sediment, river flow disturbance, and water pollution. All of these impacts can negatively affect the biodiversity of river organisms. To protect freshwater biodiversity in Indonesia’s rivers, it is important to determine how the benthic macroinvertebrate communities are influenced by key abiotic factors. This study aimed to describe, measure, and analyze the patterns of assemblage of benthic macroinvertebrate populations in connection to study sites and environmental factors in the midstream of the Citarum River, Indonesia. We also try to compare four tropical/sub-tropical biotic indices to see which one is more reliable for assessing water quality ecologically in Indonesia. We also used the Proportion of Sediment-sensitive Invertebrates (PSI) index to assess fine sediment accumulation in rivers using macroinvertebrates, since rivers impacted by dam often experience fine sediment accumulation. We found that there were differences in the benthic macroinvertebrate assemblage between stations due to different pollution levels and types of substrate. From canonical correspondence analysis, most macroinvertebrates taxa are scattered away from locations with harsh environmental conditions. This is supported by hierarchical cluster analysis, which separates stations with high taxa richness and less polluted from low taxa richness and polluted stations. Our study also showed that most of the foreign tropical and sub-tropical biotic indices were ineffective in classifying water quality in the midstream Citarum River. However, the PSI index proved to be useful in explaining the limited sensitivity of the biotic indices in evaluating water quality in rivers impacted by dams.